Peace Journalism in the 2023 Bitung Ethno-Religious Clashes - Yoedtadi, Moehammad Gafar (Jurnal Kajian Jurnalisme, 2025)
A notable incident occurred on November 25, 2023, in Bitung, North Sulawesi, when a clash between the Muslim Solidarity Front (supporting Palestine) and the Menguni Troops (supporting Israel) resulted in one death and two injuries. This phenomenon highlights the volatile nature of intergroup tensions. However, local media played a commendable role by actively engaging in conflict reconciliation efforts, instead of exacerbating the situation, and demonstrating a proactive approach to mitigating ethno-religious conflict tensions. This research aims to elucidate the practice of peace journalism as employed by local journalists in North Sulawesi, specifically in their role in reducing the ethno-religious conflict in Bitung. Using a qualitative descriptive approach and case study methodology, data were collected through in-depth interviews, observations, and document reviews. The study involved five local journalists from Bitung as research subjects, focusing on their application of peace journalism techniques in the aftermath of the conflict. The findings indicated that these journalists have a heightened awareness of the necessity for a peaceful resolution following the riots. They actively adopt and implement principles of peace journalism to quell unrest, thereby contributing to a swift resolution of conflicts. This emphasizes the critical role of journalism in fostering peace and preventing the escalation of intergroup conflicts in Indonesia. This study recommends the importance of understanding the concept of peace journalism and its application in presenting the news, especially when dealing with complex contemporary conflicts such as ethnic and religious conflicts, which are further complicated by external factors, such as the Palestine-Israel conflict.